2009
DOI: 10.1111/j.1558-5646.2009.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

The Genomic Location of Sexually Antagonistic Variation: Some Cautionary Comments

Abstract: Sexually antagonistic polymorphisms are polymorphisms in which the allele that is advantageous in one sex is deleterious in the other sex. In an influential 1984 paper, W. Rice hypothesized that such polymorphisms should be relatively common on the X chromosome (or on the W in female-heterogametic species) but relatively rare on the autosomes. Here, I show that there are plausible assumptions under which the reverse is expected to be true, and point out recent studies that give evidence for sexually antagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
351
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(375 citation statements)
references
References 34 publications
20
351
4
Order By: Relevance
“…Such phenotypic models are generally accurate for alleles that contribute additively to phenotype, under the assumption of a continuous spectrum of mutational effects and when accounting for the possibility of alternative equilibria (73). By contrast, many genetic models of sexually antagonistic traits find significant complexities with respect to the dominance interaction patterns among alleles (44,74,75). Those genetical models did not analyze the X versus autosome conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Such phenotypic models are generally accurate for alleles that contribute additively to phenotype, under the assumption of a continuous spectrum of mutational effects and when accounting for the possibility of alternative equilibria (73). By contrast, many genetic models of sexually antagonistic traits find significant complexities with respect to the dominance interaction patterns among alleles (44,74,75). Those genetical models did not analyze the X versus autosome conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous hermaphrodites generally do not possess sex chromosomes ( [16], but see [48]), so in such cases this effect would not apply. However, a recent analysis has demonstrated that the expected contribution of the sex chromosomes to sexually antagonistic genetic variation may have been overestimated and that sexually antagonistic autosomal variation can be maintained in gonochorists via sex-specific asymmetric dominance effects [49]. Sexually antagonistic alleles with asymmetric dominance effects could therefore also be maintained within simultaneously hermaphroditic populations via overdominant selection (heterozygote advantage).…”
Section: Asymmetric Fitness Effectsmentioning
confidence: 99%
“…Population genetics models are often used to evaluate the plausibility of sexual antagonism as a common mechanism for balancing selection (Kidwell et al 1977;Pamilo 1979;Curtsinger 1980;Prout 2000;Patten and Haig 2009;Unckless and Herren 2009;Fry 2010;Arnqvist 2011;Jordan and Charlesworth 2012;Patten et al 2013), and most of this theory has focused on "SA directional" selection models (but see Kidwell et al 1977;Gavrilets and Rice 2006;Mokkonen et al 2011), where only a small fraction of the conceivable parameter space for sex-specific fitness and dominance will generate balancing selection at a diploid locus (Prout 2000;Patten and Haig 2009). A broader class of fitness trade-off scenarios for balancing selection-e.g., between environments that vary over time or space (Levene 1953;Haldane and Jayakar 1963) and antagonistic pleiotropy between traits (Rose 1982;Curtsinger et al 1994)-suffers from similarly severe parameter restrictions (Prout 2000).…”
Section: Fitness Trade-offs and Opportunities For Balancing Selectionmentioning
confidence: 99%
“…Whether balanced, sexual antagonistic alleles are common within populations has important and wide-ranging biological implications for the genetic basis of quantitative traits (Rice 1984;Turelli and Barton 2004;Bonduriansky and Chenoweth 2009), genetic loads and extinction risk (Kokko and Brooks 2003;Whitlock and Agrawal 2009;Holman and Kokko 2013), mating system evolution (Seger and Trivers 1986;Albert and Otto 2005;Blackburn et al 2010;Roze and Otto 2012), and the evolution of genomes and genetic systems (Charlesworth and Charlesworth 1980;Day and Bonduriansky 2004;Ellegren and Parsch 2007;van Doorn and Kirkpatrick 2007, 2010;Mank 2009;Connallon and Clark 2010, 2011, 2013aParsch and Ellegren 2013;Wright and Mank 2013;Charlesworth et al 2014;Kirkpatrick and Guerrero 2014). Although prior theory clearly defines the parameter criteria for balancing selection by sexual antagonism (e.g., Kidwell et al 1977;Pamilo 1979;Patten and Haig 2009;Unckless and Herren 2009;Fry 2010;Patten et al 2010Patten et al , 2013Arnqvist 2011;Connallon and Clark 2012;Mullon et al 2012;Jordan and Charlesworth 2012), it remains unclear how often such conditions might be expected to arise in dioecious populations. A recent extension of Fisher's geometric model provides a theoretical framework for predicting the sex-specific distribution of mutant fitness effects (Connallon and Clark 2014), yet this the...…”
mentioning
confidence: 99%
See 1 more Smart Citation